Dexmedetomidine attenuates postoperative spatial memory impairment after surgery by reducing cytochrome C - Lina Sun; Kun Niu; Jian Guo; Jingru Tu; Baofeng Ma; Jianxiong An (BMC Anesthesiology, 2023)
Abstract Background Anesthesia and surgery can induce perioperative neurocognitive disorders (PND). Mitochondrial dysfunction has been proposed to be one of the earliest triggering events in surgery-induced neuronal damage. Dexmedetomidine has been demonstrated to attenuate the impairment of cognition in aged rats induced by surgery in our previous study. Methods Male Sprague-Dawley rats underwent hepatic apex resection under anesthesia with propofol to clinically mimic human abdominal surgery. The rats were divided into three groups: Control group, Model group and Dexmedetomidine (Dex) group. Cognitive function was evaluated with the Morris water maze (MWM), Open Field Test (OFT)and Novel object recognition task (NOR). Ultrastructural change in neuronal mitochondria was measured by transmission electron microscopy. Mitochondrial function was measured by mitochondrial membrane potential and activities of mitochondrial complexes. Neuronal morphology was observed with H&E staining and the activation of glial cells was observed by immunohistochemistry in the hippocampus. Protein levels were measured by Western blot (WB) and immunofluorescence at 3 and 7 days after surgery. Results Surgery-induced cognitive decline lasts three days, but not seven days after surgery in the model group. Transmission electron microscope showed the mitochondrial structure damage in the model group, similar changes were not induced in the Dex group. Dexmedetomidine may reverse the decrease in mitochondrial membrane potential and mitochondrial complex activity. Compared with the Control group, the expression of cytochrome c was significantly increased in model group by Western blot and immunofluorescence on days 3, but not day 7. Rats from the Model group expressed significantly greater levels of Iba-1 and GFAP compared with the Control group and the Dex group. Conclusion Dexmedetomidine appears to reverse surgery-induced behavior, mitigate the higher density of Iba-1 and GFAP, reduce the damage of mitochondrial structure and function by alleviating oxidative stress and protect mitochondrial respiratory chain, thus increasing cytochrome c oxidase (COX) expression and downregulate the expression of cytochrome c protein in the hippocampus of rats.